Pengaruh model case based learning terhadap keterampilan pemecahan masalah ditinjau dari curiosity mahasiswa PGSD UNS - Aliyah, Cantika Oktaviana Rahmatul; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Didaktika Dwija Indria, 2025)
This research aims to explore how the case-based learning model impacts problem-solving skills in relation to the curiosity levels of elementary school teacher education students at Sebelas Maret University. The study employed an experimental approach with a population consisting of second-semester students from the class of 2023. Cluster random sampling was utilized to select the participants, resulting in a sample size of 62 students. Class 2A received instruction through the case-based learning model, while class 2D experienced direct learning methods. Data was gathered using a curiosity scale and a problem-solving test. Two-way ANOVA was employed for data analysis. The findings revealed that the case-based learning model positively influences students' problem-solving skills. Additionally, curiosity was found to significantly affect problem-solving skills, yet there was no interaction effect between the case-based learning model and curiosity on students' problem-solving abilities.